Global burden of alcoholic cardiomyopathy in middle-aged men (1990–2021) and projections to 2050: a systematic analysis of the Global Burden of Disease 2021 data - Zhou, Yaqing; Liu, Tao; Meng, Yao; Ji, Zhenjun; Chen, Zhongpu; Ma, Genshan (Frontiers in Public Health, 2025)
ObjectiveAlcoholic cardiomyopathy (ACM) is a severe cardiovascular condition caused by chronic excessive alcohol consumption, leading to heart failure, increased morbidity, and mortality. This study aimed to comprehensively analyze the global burden of ACM among middle-aged males from 1990 to 2021 using the Global Burden of Disease (GBD) data. Additionally, we projected future trends until 2050 using time-series forecasting models.MethodsWe extracted ACM-related mortality, disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs) from the GBD 2021 dataset across 204 countries and territories. Temporal trends were assessed using estimated annual percentage change (EAPC). Regional clustering was performed using hierarchical analysis. Future projections were estimated using Autoregressive Integrated Moving Average (ARIMA) and Exponential Smoothing (ES) models.ResultsIn 2021, ACM caused 51,494 deaths (95% UI: 44,031–56,451), with an age-standardized death rate of 1.24 per 100,000 (95% UI: 1.06–1.36). DALYs reached 1,771,812 (95% UI: 1,521,953–1,943,500), with an age-standardized rate of 41.81 per 100,000 (95% UI: 35.97–45.8). The burden was highest in Eastern Europe, Central Asia, and Latin America. Future projections suggest a potential stabilization or gradual decline in ACM burden, though mortality and DALYs remain high in some regions.ConclusionACM remains a major global health challenge, particularly in middle-aged males. Regional disparities highlight the need for targeted alcohol control policies and improved cardiovascular healthcare. Strengthened public health interventions are crucial to mitigating ACM-related mortality and disability.